PENERAPAN ANALISIS COST VOLUME PROFIT (CVP) SEBAGAI ALAT PERENCANAAN LABA PADA CV. MARTINI PUTRA JAYA - Octavialinsi Dian Waradi; Soemaryono Soemaryono (CV. Denasya Smart Publisher, 2025)
This study aims to determine the application of Cost Volume Profit (CVP) analysis as a profit planning tool at CV. Martini Putra Jaya, a distributor of inkjet printer machines. This study uses a qualitative approach with a case study method, where data and information are collected through interviews and internal company documentation. The primary focus of this study is to evaluate how CVP analysis can be utilized in developing more structured and efficient sales strategies and profit planning, particularly for products experiencing sales fluctuations. By applying CVP calculations, the company can determine product contribution margins, break-even points (BEP), and margin of safety at which sales declines can occur, as well as conducting profit planning that can help the company achieve its profit targets. After obtaining the results of the CVP analysis, the company can develop appropriate sales strategies to increase sales and achieve profit targets. Strategies that can be implemented include slightly lowering prices and combining them with aggressive promotions to reach more segments, adding after-sales services, or offering longer warranties. The company can also offer bundling packages, such as selling a package containing a machine, ink, and initial training at a special price.